The Psychology of Women’s Health and Health Care
XI, 274 p.
Keywords: The psychology of women's health is an area traditionally controlled by male-orientated scientists, psychologists and doctors. Women by definition have been unquestioningly seen and treated as deviant from the male norm. This model has been challenged by feminist historians and sociologists but not by psychologists who seem to have implicitly accepted the medical model and emphasised the pathology in women's behaviour and emotions. In this book women's views and their experience of their own health and health care are taken seriously and analysed within a psychological and a feminist angle.